Torsion of an Abdominal-Wall Pedunculated Lipoma: A Rare Differential Diagnosis for Right Iliac Fossa Pain - Daniel Lee John Bunker; Victor George Ilie; Tushar K. Halder (Case Reports in Surgery)
Pedunculated lipomas arising from the peritoneal wall are a rare finding during abdominal surgery. These benign tumours of mesenchymal origin can arise anywhere in the body and are usually asymptomatic. We present a case of a torted, pedunculated parietal wall lipoma in the right iliac fossa that gave rise to a clinical diagnosis of appendicitis. To our knowledge, such a case has never been reported in the literature previously. We suggest that torsion of a pedunculated parietal lipoma is a rare differential of acute abdominal pain.